Innovative Entrepreneurship and Economic Sustainability in the Selected Private Universities in Nigeria: The Pre and Post COVID-19 Comparative Analysis - Babasanya, Adeyemi Olayiwola; Ologundudu, Mojeed .M.; Oluyomi, Oluwatosin Olatunji (ABC Journal of Advanced Research, 2022)
Extant studies have found that entrepreneurship remains immune from business uncertainties to achieve economic Sustainability. Although fewer studies show that innovative entrepreneurship is more than creating an enterprise, a destructive process is an impetus in achieving economic Sustainability amid business uncertainties. To this end, this study empirically examines the impact of innovative entrepreneurship on economic Sustainability in the selected private universities in Nigeria during the Pre and Post COVID-19 era. Five private universities in Nigeria were selected from the four phases of private universities in Nigeria since the deregulation of university education in 1999. In addition, descriptive statistics results from the last five Universities Webometrics rankings found that Covenant University only had a persistent economic sustainable trend between 2016 to 2019, while all the selected private universities except Covenant University were not remarkable in economic Sustainability amid the post-COVID-19 era between 2019 and 2020 in this study. To this end, the study concluded that before COVID-19, most selected private universities failed to display innovative entrepreneurship vis-à-vis lecturers to students teaching ratio, routine teaching methods, stagnated learning techniques, limited sectoral competitions, presence rank, impact rank, openness rank, excellence rank, and among others. Therefore, establishing a university is entrepreneurship but will not guarantee economic Sustainability if not driven by evolutionary innovation amid the post-COVID-19 and beyond uncertainties. Thus, the study recommends all stakeholders, including the University management, staff members, and the government, to be evolutionary in their mindset to achieving economic Sustainability amid COVID-19 and beyond among Nigerian private universities.